Efecto de fungicidas sistémicos y protectores en el control de moniliasis y escoba de bruja en cacao - Vélez Balderramo, Erika Talia (2023)
The objective of the present investigation was to test the effect of systemic and protective fungicides in the control of moniliasis and witches' broom in cocoa. The research was carried out in the cocoa lot of the Research, Teaching and Liaison Unit of the Agricultural Engineering Department. A randomized complete block design (RCBD) was used, 500 plants were selected and distributed in 20 experimental units, five treatments and four replicates. The frequency with which the chemical products were applied was 30 days, with the doses recommended by the manufacturers (Azoxystrobin, Cyproconazole, Copper Sulfate Pentahydrate at 2ml/l and Chlorothalonil at 4gr/l). Phytosanitary and production variables were evaluated based on these fungicides. The frequency of data recording was every month. The analysis of variance (ANOVA) was performed using Tukey's test 0.05, being semiannual for the phytosanitary variable and annual for the production variables. At the end of the two evaluation periods, the treatment that showed the greatest effectiveness on disease incidence was T1 (Azoxystrobin). This treatment showed efficacy on Moniliophthora roreri and Moniliophthora perniciosa, influencing production, which reached the highest yield (kg/ha/year).